PERKUATAN DAN STABILISASI BADAN JALAN MENGGUNAKAN SISTEM PLAT SPUN PILE - Maha Agung, Putera Agung; Tsabita, Dea Putri (Construction and Material Journal, 2020)
AbstractSome damages of the Jalan Lintas Selatan Road, Suradita-Kranggan has occured every year with the identical failure cycle. One of the effort to make problem solving is to replace the base of road body construction with a concrete plate construction supported by circular pre-stressed concrete pile foundation (spun pile) system. The system will carry on the upper structure or embankment (subgrade) since the below of the structure exists soft soil layers and the depth of hard layer soil reachs more than 10 m. Later on, all vertical and horizontal forces including moments caused by the external loads can be retained by the plate and spun pile foundation system. The purpose of the study is to calculate the bearing capacity, negative friction force, settlement of spun pile group with using field test data (SPT and CPT); and diameter variation of pile is 30 cm to 50 cm. From calculations with the average length of 1400 cm and diameter of 50 cm can be determined bearing capacity of 298.9 tons by SPT and 504.3 tons by CPT data, respectively. Then, lateral bearing capacity is 168.5 tons (free pile head) and 344.2 tons (fixed pile head). The settlement occurred of a single pile foundation is 9.40 cm. The results of negative friction resistance were obtained is 81.9 tons. The group piles is designed of 2 (two) rows and 3 (three) columns and can be safe for receiving the construction and traffic loads. Based on the analysis results, the concrete plate and spun pile system has fullfilled to design criteria. Keywords: spun pile, bearing capacity, negative friction, settlement, pile group.AbstrakKerusakan pada Jalan Lintas Selatan, Suradita-Kranggan terjadi setiap tahun dengan siklus kegagalan yang sama. Salah satu upaya penyelesaian masalah tersebut adalah mengganti landasan konstruksi badan jalan dengan plat beton yang didukung oleh sistem pondasi tiang pancang bulat beton prategang (spun pile). Sistem ini akan memikul struktur atas atau timbunan (subgrade) karena di bawah struktur terdapat lapisan tanah lunak dan kedalaman tanah keras mencapai lebih dari 10 m. Nantinya, semua beban vertikal, horizontal berikut momen akibat beban luar dapat ditahan oleh sistem plat dan pondasi spun pile. Tujuan studi ini adalah untuk menghitung daya dukung, gaya gesek negatif, dan penurunan dari kelompok tiang menggunakan data hasil uji lapangan (SPT dan CPT), dan variasi diameter tiang adalah sebesar 30 cm sampai 50 cm. Dari hasil perhitungan dengan panjang rata-rata 1400 cm dan diameter tiang 50 cm dapat ditentukan daya dukung sebesar 298,86 ton (data SPT) dan 504,3 ton (CPT data) secara berurutan. Kemudian, daya dukung lateral sebesar 168,5 ton (kepala tiang bebas) dan sebesar 344,2 ton (kepala tiang terjepit). Penurunan tunggal rata-rata yang terjadi adalah sebesar 9,40 cm. Hasil tahanan gesek negatif diperoleh sebesar 81,9 ton. Kelompok tiang yang direncanakan adalah terdiri 2 baris tiang dan 3 kolom tiang dan aman untuk menerima beban konstruksi dan beban lalu lintas. Berdasarkan hasil analisis, sistem plat dengan spun pile telah memenuhi kriteria desain. Kata kunci: spun pile, daya dukung, gaya gesek negatif, penurunan, grup tiang.